THEORETICAL AND METHODOLOGICAL PRINCIPLES OF FORMATION AND USE OF THE MANAGEMENT MECHANISM FOR ENSURING THE FINANCIAL AND ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES - KUTSENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The functioning and development of enterprises takes place under the condition of changes in the influence of external environmental factors, the emergence of crisis phenomena, threats that have a negative impact on the financial condition, the results of operations, can cause a sharp reduction in indicators. It is various threats and crisis phenomena that can lead to inefficient use of financial resources and the emergence of bankruptcy at enterprises. It was determined that economic security plays an important role for enterprises, which guarantees their protection from the negative impact of internal and external environmental factors, minimizes their impact, and allows to eliminate identified threats. Along with economic, an important role is played by financial security, which is aimed at ensuring the rational use of financial resources, reducing costs, and improving the financial situation. All this determines the importance of ensuring the financial and economic security of enterprises, which is possible by using a set of tools. The need to introduce an improved management mechanism for ensuring financial and economic security, which has theoretical and practical significance, will allow the formation of measures to neutralize the influence of market environment factors, threats, guarantee a high level of security, restore performance indicators, determine the sequence of actions to ensure the desired level of security, methods of countermeasures crisis phenomena. The management mechanism for ensuring the financial and economic security of enterprises consists of interconnected stages, elements, is implemented by following approaches that allow it to be used successfully and achieve the established goal. As part of the mechanism, measures are proposed to neutralize threats, risks, and ways to restore the level of financial and economic security of enterprises, which will guarantee successful functioning in the short and long term.
Keywords: economic security; financial security; financial and economic security; management; management mechanism; market environment; threats; enterprises